Performance Evaluation of a Cowpea Thresher at Various Moisture Contents (International Journal of Technology and Management Research, 2020)
To improve the quality of threshed cowpea (Vigna unguiculata L.), produced by rural farmers in Ghana, and determine the best machine-crop parameters combination for optimum performance, a cowpea thresher was developed and evaluated at different moisture contents. The cowpea after harvesting was divided into five units and dried to 20.7, 18.4, 15.5, 13.5 and 12.6 % seed moisture contents. The effect of seed moisture contents on threshing quality was assessed at 735 rpm rotor speed using the white with black eye cowpea. The performance test showed that 12.6 % had the highest throughput of 77.56 kg/h with the lowest of 66.28 kg/h from the 20.7%. The seed damage ranged from 1.64 to 9.46 % and threshing efficiency from 93.11 to 99.40 %. Analyses done at 5% level of significance indicated no significant difference in the throughput and threshing efficiencies. However, seed damage had significant difference. Subsequently, analysis performed on the data for seed loss of 12.6 and 13.5 % which were the best performing moisture contents showed no significant differences. Therefore, seed moisture contents less than 13.5 % and rotor speeds less than 735 rpm are the crop- machine parameters combination for optimum thresher performance.Key words: Design; Throughput; Impact Force; Seed Loss; Simulation